Diseminasi Filsafat Pendidikan Islam Berdasarkan Pengalaman Praktis di Indonesia pada Forum Internasional di KIDU Malaysia - Fahri Hidayat; Binti Khairuddin, Haniza; Sumarto, Sumarto; Syafryadin, Syafryadin; Yahya, Slamet; Pratiwi, Risa (PELITA NUSA TENGGARA, 2025)
Malaysia is one of the countries with the largest Muslim population in Southeast Asia after Indonesia. Kedah, often referred to as the “Serambi Makkah,” has a strong tradition of Islamic education. However, modernization requires institutions such as Kolej Islam Darul Ulum (KIDU) to renew their curricula to stay relevant to contemporary scientific development. The main challenge faced by the partner institution is designing an integrated curriculum that connects Qur’anic sciences with modern disciplines. Indonesia has extensive experience in knowledge integration through conceptual frameworks and institutional practices. This dissemination program aims to provide academic insights on democracy, the philosophical framework of Islamic education, and integrated curriculum development relevant to KIDU’s needs. The method used is collaborative and participatory through academic lectures, dialogic forums, and institutional exchange. The program began with the signing of a Memorandum of Understanding (MoU) between the Postgraduate School of UIN Prof. K.H. Saifuddin Zuhri (UIN SAIZU) and KIDU as a basis for strengthening the tridharma collaboration. KIDU presented its current academic policy through the development of an integrated curriculum based on a scientific exegesis of Juz 30. The presenter delivered three key themes: democracy and Islamic education in post-reform Indonesia, integrative curriculum characteristics, and the religious-nationalist orientation of Indonesian Islamic education. The results show strategic contributions to institutional capacity building, academic networking, and collaborative research prospects. The program implies the applicability of integrative models and the sustainability of transnational academic dialogue. In conclusion, this dissemination successfully created an exchange platform for developing modern Islamic curricula in Southeast Asia.